Mechanical Behavior of Q460 High-Strength Steel under Low-Cycle Fatigue Loading - Xue Han; Min Chang; Haifeng Li; Hualin Cao; Baoan Cao (Advances in Civil Engineering)
To investigate the mechanical properties of Q460 high-strength steel under repeat tensile loading, 45 specimens were prepared for repeated tensile tests. The specimens are tested under 16 different loading regimes. The effects of welded joints, specimen shape and dimensions, and loading modes on the mechanical properties of the steel were analyzed. In addition, a finite element model of the specimen under cyclic load was established with ANSYS and the numerical results were compared with those of the experimental tests. This finite element model can accurately simulate the deformation characteristics of Q460 steel specimens. Experimental studies have found that the welded joints have adverse effects on the mechanical properties of this material. The cumulative effect of fatigue damage on the welded specimens was significant, and the ductility of welded specimens was poor under cyclic loading. The loading mode had a major impact on the results of the material tests. As the number of loading cycles increased, the cumulative effect of fatigue damage on the specimens was more evident, and the length, size, and cross-sectional shape of the tensile zone all affected the stiffness of the specimen. Finally, based on the experimental research and numerical analysis results, a design formula for the tensile strength of Q460 steel under repeated loading was proposed. This formula can serve as a reference for the application of Q460 steel in seismic engineering.